2017
DOI: 10.1111/mcn.12480
|View full text |Cite
|
Sign up to set email alerts
|

Early pregnancy body mass index modifies the association of pre‐pregnancy dietary patterns with serum polyunsaturated fatty acid concentrations throughout pregnancy in Brazilian women

Abstract: Dietary patterns (DPs) have been described as an important factor that may influence polyunsaturated fatty acid (PUFA) concentrations and body mass index (BMI) during pregnancy. We aim to evaluate the association between pre-pregnancy DPs and serum PUFA percentages throughout pregnancy considering early pregnancy BMI as a possible effect modifier. A prospective cohort of 154 pregnant women was followed (5th-13th, 20th-26th, and 30th-36th gestational weeks). Serum PUFA concentrations (total n-3 and total n-6, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…A limited number of such studies during pregnancy are reported. In a cohort of 154 women, Benaim et al [ 27 ] found that pre-pregnancy dietary patterns, as assessed by an FFQ six months prior to gestation, loading high for “healthy” foods were associated with increased n -3 fatty acid status during pregnancy. This “healthy” dietary pattern included foods such as vegetables, fruits, fruit juices, fish and dairy products.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A limited number of such studies during pregnancy are reported. In a cohort of 154 women, Benaim et al [ 27 ] found that pre-pregnancy dietary patterns, as assessed by an FFQ six months prior to gestation, loading high for “healthy” foods were associated with increased n -3 fatty acid status during pregnancy. This “healthy” dietary pattern included foods such as vegetables, fruits, fruit juices, fish and dairy products.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the results of the current study as we concluded a dietary pattern loading high for fish and fruit was associated with increased DHA and total n -3 PUFA concentrations. It has been suggested that in a varied diet, foods not regarded to be a rich source of a certain nutrient may increase nutrient bioavailability, with nutrients interacting to increase or decrease bioavailability of one another, alluding to a food matrix effect [ 27 , 31 ]. They found that dietary patterns containing foods that do not have a significant PUFA content such as cabbages, root vegetables, coffee and tea were associated with increased plasma and red blood cell n -3 PUFA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MHFD models rely on diets usually enriched in SFAs with a high n-6/n-3 PUFA ratio, reflecting the Western diet. Indeed, obese pregnant women consistently have an elevated n-6/n-3 PUFA ratio ( Benaim et al, 2018 ; Vidakovic et al, 2015 ). Interestingly, a study in Hawaiian pregnant women, whose fish consumption is likely higher than in the typical Western diet, showed that obese women had higher n-3 PUFA levels than obese women from Ohio, albeit lower than their lean counterparts ( Alvarado et al, 2018 ).…”
Section: The Immunomodulatory Roles Of Fatty Acidsmentioning
confidence: 99%